IMPLEMENTASI INOVASI OLAHAN PANGAN YANG MENGGUNAKAN DAUN KELOR GUNA MENINGKATKAN MASSA TUBUH BALITA STUNTING DAN LITERASI GIZI SECARA DIGITAL - Zasmeli Zasmeli Suhaemi Suhaemi; April Zahmi; Sayendra Safaria, S.Kom., M.Kom; Mayuasti Mayuasti; Firdaus Firdaus (LPPM Universitas Andalas, 2024)
Stunting gives negative impacts for children’s cognitive developments, emotions, behaviors, education, productivity, and disease when they grow up. Hence, one of the efforts to reduce the prevalence of stunting is to increase nutritional knowledge and functional food processing skills for stunted toddlers’ mothers. This activity was applied in the Family Group at the East Padang District Nutrition House collaborating with the East Padang District Health Center. The previous research findings showed that the Protein and Mineral of Moringa leaf Nuggets, one of the processed food innovations, has exceeded the nutritional standards according to the Republic of Indonesia Minister of Health Regulation Number 51 of 2016 concerning Nutritional Supplementation Product Standards. The purpose of this activity is to increase the parents’ understanding of nutrition. Because of this digital era, it is needed to educate and assist stunted toddlers’ parents through digital literacy regarding nutritional standards for toddlers and food processing training to increase toddlers' body mass. There are three stages done in applying technological methods are 1) Socialization; 2) Training; 3) Evaluation. The evaluation’s result of providing knowledge and training to stunted toddlers’ mothers is that the knowledge and skills of stunted toddlers’ mothers is increased by 86.67%. In short, training for stunted toddlers’ mothers regarding innovations in Moringa leaf food processing that are nuggets, meatballs and Fantasy tofu, additional food for stunted toddlers, has significantly increased mothers’ knowledge and skills.